Cases reports: Unintended anti‐doping rule violation after dorzolamide use several months prior to a doping control. Issue 10 (30th August 2021) - Pokrywka, Andrzej; Skrzypiec‐Spring, Monika; Krzywański, Jarosław; Rynkowski, Michał; Saugy, Martial; Faiss, Raphael
Abstract : The use of specific medicine up to several months before a doping control is not be reported on the doping control form, while the drug could then still be detectable in urine in case of a very slow elimination. It may lead to a positive test result. For example, dorzolamide, a carbonic anhydrase inhibitor for topical ophthalmic application, has a very slow elimination rate via the renal route (half‐life > 4 months). This substance can be a source of unintended anti‐doping rule violations.